2011
DOI: 10.1016/j.immuni.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-Editing Protein A20 Prevents Dendritic Cell Activation, Recognition of Apoptotic Cells, and Systemic Autoimmunity

Abstract: Dendritic cells (DCs) regulate both immunity and tolerance. Here we have shown that the ubiquitin editing enzyme A20 (Tnfaip3) determines the activation threshold of DCs, via control of canonical NF-κB activation. Tnfaip3(fl/fl)Cd11c-cre(+) mice lacking A20 in DCs demonstrated spontaneous proliferation of conventional and double-negative T cells, their conversion to interferon-γ (IFN-γ)-producing effector cells, and expansion of plasma cells. They developed ds-DNA antibodies, nephritis, the antiphospholipid sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
213
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(223 citation statements)
references
References 46 publications
7
213
3
Order By: Relevance
“…This provides a framework for understanding the role of A20 in suppressing B-cell lymphomas, which is suggested by human genetic studies (36,96,161). Other studies have found critical functions for A20 in dendritic cells (83,126), macrophages (167), and intestinal epithelial cells (265).…”
Section: Otu Familymentioning
confidence: 84%
“…This provides a framework for understanding the role of A20 in suppressing B-cell lymphomas, which is suggested by human genetic studies (36,96,161). Other studies have found critical functions for A20 in dendritic cells (83,126), macrophages (167), and intestinal epithelial cells (265).…”
Section: Otu Familymentioning
confidence: 84%
“…The crosstalk between DCs and myeloid cells is likely mediated by FLT3L, given the key role of FLT3L in myeloid cell expansion (21,60), although this action does not appear to affect myeloid populations in the BM. Recently, expansion of myeloid populations and increases of serum FLT3L levels have been reported in mice with DC-selective deletion of A20, a negative regulator of NF-κB signaling (66,67). However, unlike DCs lacking TAK1, A20-deficient DCs show enhanced responses to CD40 and RANKmediated survival signals and trigger profound activation of T cells and B cells and development of autoimmunity (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, expansion of myeloid populations and increases of serum FLT3L levels have been reported in mice with DC-selective deletion of A20, a negative regulator of NF-κB signaling (66,67). However, unlike DCs lacking TAK1, A20-deficient DCs show enhanced responses to CD40 and RANKmediated survival signals and trigger profound activation of T cells and B cells and development of autoimmunity (66,67). Therefore, immune homeostasis under steady state is dependent upon molecular signals in DCs, especially a delicate threshold of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of signal containment in A20-deficient mice results in severe inflammation and lethality that is triggered by MyD88-dependent TLR signaling initiated by the commensal flora (7,8). Cell type-specific deletion of A20 in immune cells and other tissues like intestinal epithelial cells and skin further confirmed its crucial role in the maintenance of tissue homeostasis and to prevent inflammatory diseases including autoimmunity (9)(10)(11)(12)(13)(14)(15). In B cells, loss of A20 causes hyperreactivity, general immune activation, and the production of autoantibodies (10,11,16).…”
mentioning
confidence: 90%